Steam-based natural and social sciences learning materials integrated with local culture for elementary schoolsl Culture for Elementary Schools - Erna Zumrotun; Sabar Narimo; Harun Joko Prayitno (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
Natural and Social Sciences learning in elementary schools requires instructional materials that integrate scientific and social concepts while remaining relevant to students’ cultural environments. Existing materials frequently present local culture as supplementary information and provide limited guidance for interdisciplinary learning. This study aimed to develop the Pesona Jepara textbook, which integrates Jepara’s local culture into Grade V Natural and Social Sciences learning through a Science, Technology, Engineering, Arts, and Mathematics approach. The study employed a research and development design involving the analysis, design, and development stages of the ADDIE framework. Product feasibility was evaluated by three experts in elementary education, elementary science education, and elementary social studies education using a four-point validation instrument covering nine aspects. Quantitative data were analysed descriptively, while expert comments guided product refinement. The textbook obtained an overall mean score of 3.78 out of 4.00, equivalent to 94.53%, and was categorised as very feasible. Conceptual accuracy, STEAM implementation, and the integration of natural and social sciences received the highest percentages of 97.25%. Design practicality received 88.25% but remained within the very feasible category. Classroom trials are required to establish the product’s practicality and effectiveness.